Development of a pragmatic framework to help food and drink manufacturers select the most sustainable food waste valorisation strategy. (1st October 2019) - Stone, Jamie; Garcia-Garcia, Guillermo; Rahimifard, Shahin
Abstract: Food waste is a significant contemporary issue in the UK, with substantial environmental, social and economic costs to the nation. Whilst efforts to reduce food waste are laudable, a significant proportion of food and drink manufacturer waste is unavoidable. On the one hand, there is a drive from industry to reclaim as much value from this waste as possible, for example, by conversion to valuable products in what is known as "valorisation". At the same time, growing social and legislative pressures mean that any attempts to valorise food waste must be performed in a sustainable manner. However, for every company and its specific food wastes, there will be multiple valorisation possibilities and few tools exist that allow food and drink manufacturers to identify which is most profitable and sustainable for them. Such a decision would need to not only consider environmental, social and economic performance, but also how ready the technology is and how well it aligns with that company's strategy. In response, this paper develops and presents a hybrid framework that guides a company in modelling the volumes/seasonality of its wastes, identifying potential valorisation options and selecting appropriate indicators for environmental, social and economic performance as well as technological maturity and alignment with company goals. The framework guides users in analyzing economic and environmental performance using Cost-Benefit Analysis and Life Cycle Assessment respectively. The results can then be ranked alongside those for social performance, technological maturity and alignment with company goals using a weighted sum model variant of Multi-Criteria Decision Analysis to facilitate easy visual comparison. This framework is demonstrated in the form of a case study with a major UK fruit consolidator to identify the optimal strategy for managing their citrus waste. Possibilities identified included sale of imperfect but still edible waste via wholesale at a significantly reduced profit and the investment in facilities to extract higher value pectin from the same waste stream using a microwave assisted pectin extraction process. Results suggest that continued sale of waste to wholesale markets is currently the most beneficial in terms of economic viability and environmental performance, but that in the medium to long term, the projected growth in the market for pectin suggests this could become the most viable strategy. Highlights: When food waste cannot be avoided, valorisation can increase company resilience. Valorisation strategies must try to avoid negative supply chain ramifications. The SWaVI pragmatic framework allows companies to identify their optimal valorisation route. The SWaVI pragmatic framework facilitates initial selection, not implementation of valorisation.